2004
DOI: 10.1208/pt050453
|View full text |Cite
|
Sign up to set email alerts
|

Particle size and temperature effect on the physical stability of PLGA nanospheres and microspheres containing Bodipy

Abstract: The purpose of this study was to investigate the effect of particle size, storage temperature, and duration of storage on the physical stability and morphology of polylactic-co-glycolic acid (PLGA) nanospheres and microspheres. PLGA nanospheres and microspheres containing the fluorescent dye, Bodipy, were prepared in varying sizes by controlling the method and degree of agitation during the emulsification phase of preparation. Mean diameters of the particles were measured by dynamic light scattering. To evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 22 publications
2
34
0
1
Order By: Relevance
“…Prior studies indicated the provocative role of increasing storage temperature on the extent of coalescence of nanosized particles (18). As seen in the photographic images in Fig.…”
Section: Sedimentation Behavior Of the Formulations In Storage Conditmentioning
confidence: 75%
“…Prior studies indicated the provocative role of increasing storage temperature on the extent of coalescence of nanosized particles (18). As seen in the photographic images in Fig.…”
Section: Sedimentation Behavior Of the Formulations In Storage Conditmentioning
confidence: 75%
“…As a general observation, it might be said that the thermal and magnetic properties together with biocompatibility or biodegradability properties might allow for their use in several of the proposed biomedical applications, thus avoiding the problem of unexpected and unpredictable physical changes that can happen when they are processed during their production (such as thermal stability changes due to PLGA solubilization/lyophilization or iron oxide interaction), when applied to the human body, or when they are stored for later use. Several studies have demonstrated the importance of thermal characterization of bulk PLGA and materials based on such polymer, for better understanding of its stabilities, degradation, among other properties [20][21][22] . In this work, hollow PLGA nanospheres and PLGA magnetic nanospheres (with maghemite entrapment) were characterized.…”
mentioning
confidence: 99%
“…47 The absence of PLGA NP aggregation in our experiments suggests that the amount of solvent (chloroform) in the sample after interfacial instability is too low to enable temperatureinduced aggregation.…”
mentioning
confidence: 76%